Exploring socio-demographic and geospatial variation in human papillomavirus vaccination uptake in Virginia. Issue 38 (7th September 2021) - Staples, Jeanine N.; Nelamangala, Samhita L.; Morris, Sean; Wells, Kristen
Highlights: Significant regional variability in HPV vaccine coverage exists in Virginia. HPV vaccine series initiation is lower in more rural impoverished regions of Virginia. HPV vaccine series completion is lower in more affluent regions of Virginia. Community-based interventions must consider the specific needs of the region. Abstract: Significant variation in human papillomavirus (HPV) vaccine coverage exists across the United States. A closer look at state and region-specific coverage is necessary to identify potentially modifiable disparities. Using ArcGIS software, we identify geospatial variation in HPV vaccine coverage in the state of Virginia and examine the relationship between various socio-demographic indicators and HPV vaccination uptake. HPV vaccination rates among adolescents 11 to 17 years as of 07/01/2018 were retrieved at the zip-code level from the Virginia Immunization Information System and chloropleth maps produced. The ArcGIS Hot Spot Analysis tool identified spatial clusters of zip codes with high and low vaccination rates. Population characteristics and socioeconomic indicators were retrieved from the 2010 United States Census and compared between statistically significant clusters of higher or lower than expected vaccination rates. Regions with significantly lower initiation rates were less populated, less educated, and had a lower median household income (MHI) with higher rates of poverty and unemployment. Among male adolescents, these areas had a significantly lower density of primary care providers and smaller African American and Hispanic populations. In contrast, regions with significantly lower series completion were more populated and had a higher MHI, but there was no difference in provider density or minority population. Ultimately, regional socioeconomic indicators are significant predictors of HPV vaccination, but have contrasting implications for series initiation and completion. Targeted interventions and safety net programs have traditionally focused on the socioeconomically disadvantaged, however it is the more affluent communities that may be struggling with series completion.